Visitor Motives of Interest to Use Dailysocial.id as Micropayment News Portal - Mentari Puspadini; Pandan Yudhapramesti; Gema Nusantara Bakry (School of Journalism, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
The use of micropayment methods in the media industry has proven to be well received by media audiences in Europe and the United States. Even so, there has been no further research regarding consumption patterns of media audiences in Indonesia for this payment method. This study aims to measure how much the motive of visitors is in their interest in accessing DailySocial.id as a micro-paid news portal by using the uses and gratifications 2.0 theory which has a typology of the MAIN model (modality, agency, interactivity and navigability. Through a descriptive quantitative research survey method, researchers process data from 349 respondents who are members of the DailySocial.id media audience. As a result, the navigability motive is the most powerful reason that drives audiences to consume the media, followed by modality motives in second place, interactivity in third place and agency in last place. Navigability is the biggest motive which shows that the audience access DailySocial.id because they can feel free in exploring all the information on the site, so they feel entertained. That feeling of entertainment makes the fun indicator the main gratification that audiences seek when accessing DailySocial.id as micro-paid news. In addition, it is evident that the majority of audience (76%) are more likely to be interested in buying micro-paid articles. Meanwhile, the frequency and duration of access are the two things that most contribute to fulfilling user motives in their interest in accessing DailySocial.id as a micro-paid news portal.